Queering healthcare with technology?—Potentials of queer-feminist perspectives on self-tracking-technologies for diversity-sensitive healthcare - Ellerich-Groppe, Niklas; Ott, Tabea; Puzio, Anna; Weigold, Stefanie; Müller, Regina (Zeitschrift für Ethik und Moralphilosophie (ZEMO) – Journal for Ethics and Moral Philosophy, 2024)
Self-tracking-technologies can serve as a prominent example of how digital technologies put to test established practices, institutions, and structures of medicine and healthcare. While proponents emphasize the potentials, e.g., for individualized healthcare and new research data, opponents stress the risk that these technologies will reinforce gender-related inequalities. While this has been made clear from—often intersectional—feminist perspectives since the introduction of such technologies, we aim to provide a queer-feminist perspective on self-tracking applications in healthcare by analyzing three concrete cases. In this way, we want to show why such a perspective is helpful in assessing self-tracking technologies and how such a perspective might contribute to a queering of healthcare. After a short introduction to self-tracking in healthcare and the corresponding risks of reproducing gender-related inequalities, we introduce queer bioethics as a methodology to examine structural discrimination and marginalization in bioethical research. We apply this framework in the analysis of three exemplary self-tracking applications from the areas of nutrition/fitness, reproductive health, and mental health. In the subsequent discussion of these results against the backdrop of already existing queer-sensitive technologies, we identify an equal access, a subversive design, an inclusive database, and a diversity-sensitive and discriminatory-critical definition of purposes as well as individualized usage possibilities as first possible starting points for a queering of self-tracking applications. Finally, we draw conclusions, how such a critical perspective on self-tracking applications might also contribute to a queering of the healthcare system at a structural leve
Keywords: Self-tracking